Accessibility Improvement Strategy to Support Tourism De-velopment of Lau Kawar Lake - Riyandi Hanafiah; Cut Nuraini; Abdi Sugiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Lau Kawar Lake, a natural tourism area located on the slopes of Mount Sinabung in Karo Regency, North Sumatra, holds significant potential for the development of nature and culture-based tourism. However, the growth in tourist visits has not yet met expectations due to limited accessibility across various dimensions. This study aims to formulate strategies for improving physical, informational, and institutional accessibility in support of sustainable regional development.The research adopts a mixed methods approach, emphasizing primary data collection through field observations, interviews with key stakeholders and village officials, as well as surveys of 60 tourist respondents. Findings reveal that, overall, the three dimensions of accessibility are still rated as